Targeting Senescence with Apigenin Improves Chemotherapeutic Efficacy and Ameliorates Age‐Related Conditions in Mice - Hongwei Zhang; Qixia Xu; Zhirui Jiang; Rong Sun; Qun Wang; Sanhong Liu; Xin Luan; Judith Campisi; James L. Kirkland; Weidong Zhang; Yu Sun (Advanced Science)
Abstract Cellular senescence is a cell fate triggered by stressful stimuli and displays a hypersecretory feature, the senescence‐associated secretory phenotype (SASP). Senescent cell burden increases with aging and contributes to age‐related organ dysfunction and multiple chronic disorders. In this study, a large scale screening of a natural product library for senotherapeutic candidates is performed. Apigenin, a dietary flavonoid previously reported with antioxidant and anti‐inflammatory activities, exhibits capacity for targeting senescent cells as a senomorphic agent. This compound blocks the interactions between ATM/p38MAPK and HSPA8, preventing the transition of an acute stress‐associated phenotype (ASAP) toward the SASP. Mechanistically, apigenin targets peroxiredoxin 6 (PRDX6), an intracellular redox‐active molecule, suppressing the iPLA2 activity of PRDX6 and disrupting downstream reactions underlying SASP development. Apigenin reduces the severity of cancer cell malignancy promoted by senescent stromal cells in culture, while restraining chemoresistance when combined with chemotherapy in anticancer regimens. In preclinical trials, apigenin improves the physical function of animals with a premature aging‐like state, alleviating physical frailty and cognitive impairment. Together, the study demonstrates the feasibility of exploiting a natural compound with senomorphic capacity to achieve geroprotective effects by modulating the SASP, thus providing a baseline for future exploration of natural agents for alleviating age‐related conditions.